Pengaruh Kombinasi Expressive Writing Therapy dan Afirmasi Positif Terhadap Kecemasan pada Pasien Hemodialisis di RSUD Tidar Kota Magelang: Kombinasi Expressive Writing Therapy dan Afirmasi Positif - Meinanda Enjang Wulansari; Angga Sugiarto; Erna Erawati; Dwi Ari Murti Widigdo (Universitas Widya Nusantara, 2025)
Patients undergoing hemodialysis often experience anxiety due to the unpredictable nature of their illness, raising concerns about potential recovery and dependence on dialysis machines. Addressing anxiety is crucial, as it significantly impacts patients' quality of life. The combination of expressive writing therapy and positive affirmations is a non-pharmacological approach to managing anxiety by allowing individuals to express their feelings and thoughts through writing and reinforce their self-esteem through positive statements. This study aims to investigate the effect of the combination of expressive writing therapy and positive affirmations on anxiety in hemodialysis patients at RSUD Tidar, Magelang. A quantitative research design was employed, utilizing a quasi-experimental approach with a pretest-posttest design and a control group. Purposive sampling was used, resulting in a total of 40 respondents. The Hamilton Anxiety Rating Scale (HARS) was utilized as the measurement instrument. In the intervention group, the Paired T-test yielded a p-value of 0.000 (p < 0.005). In the control group, the Wilcoxon test resulted in a p-value of 0.000 (p > 0.05). The Mann-Whitney U test indicated a p-value of 0.000 (p < 0.05) when comparing the intervention and control groups. These findings demonstrate that the combination of expressive writing therapy and positive affirmations is effective in reducing anxiety among hemodialysis patients. Keyword : Anxiety; expressive writing therapy; hemodialysis; positive affirmations